2018
DOI: 10.1016/j.indmarman.2018.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Brand worlds: Introducing experiential marketing to B2B branding

Abstract: Experiential marketing instruments and the extraordinary experiences they provide are one of the strongest means of branding in B2C. Inter alia as brand worlds, they also exist in B2B marketing practice, but have only received limited attention from the B2B branding perspective. Differences between B2C and B2B branding raise questions regarding why B2B companies operate brand worlds, what they consist of, what their nature is, and how they are experienced. We build on a rich, comprehensive sample of 37 expert … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 113 publications
1
33
0
3
Order By: Relevance
“…Schmitt [10] indicated that experience is a response of the consumer to the occurrence of a certain stimulating event, usually induced by direct observation or involvement of the event rather than caused spontaneously. To reinforce customer experience is to strengthen the rights and values of the brand [23].…”
Section: Experiential Marketingmentioning
confidence: 99%
“…Schmitt [10] indicated that experience is a response of the consumer to the occurrence of a certain stimulating event, usually induced by direct observation or involvement of the event rather than caused spontaneously. To reinforce customer experience is to strengthen the rights and values of the brand [23].…”
Section: Experiential Marketingmentioning
confidence: 99%
“…Main question for most of the organizations, especially on the B2B market, is maintaining efficiency of activity of the company and retention of a brand's position. It should be noted that there are differences between brand creation on a B2C market and on a B2B market [2]; however, preservation of the current clients of the organization and ensuring their loyalty is a crucial component of any company's success [3].…”
Section: Introductionmentioning
confidence: 99%
“…B2C brand world visitors mainly seek for autotelic, hedonic, and emotional experiences based on entertainment, information, flow, relaxation, diversity, escapism, community and a general sense of well-being and appreciation by the operating company. Their visit is often unrelated to a specific buying situation and motivated mostly by the visitors themselves (Kirchgeorg et al, 2012;Opaschowski, 2000;Österle et al, 2018a, 2018bZentes et al, 2014). Business visitors to B2B brand worlds, on the other hand, have more utilitarian expectations.…”
Section: Brand Worlds In Industrial Marketingmentioning
confidence: 99%
“…Like experiences in tourism or B2C brand worlds, visitor experiences in such B2B brand worlds are co-created on-site (Campos, Mendes, Valle, & Scott, 2015;Carù & Cova, 2007;Dolbec & Chebat, 2013;Kozinets et al, 2004;Österle et al, 2018a). Two things are at the core of this experience co-creation in B2B brand worlds: the B2B brand world experiencescape, which reflects the operating company's contribution, and the embodied cognition of the B2B brand world, reflecting the visitors' contribution to how they experience the B2B brand world (Österle et al, 2018a).…”
Section: Brand Worlds In Industrial Marketingmentioning
confidence: 99%
See 1 more Smart Citation